Le droit d’accès à la nature en Europe du Nord : partage d’un capital environnemental et construction d’un espace contractuel - Camille Girault (VertigO)
The right of public access is a principle of Northern Europe, employed especially in Iceland, Norway, Sweden and Finland, which allows anybody to roam and benefit from natural spaces regardless of their land status. Crossing a meadow, picking mushrooms and berries in the forest, setting up a tent on a grassland, hiking all the trails and canoeing on any lake are actually common environmental services and amenities for all according to this customary law, which considers nature as a public good. Considering this right of access through the concept of environmental capital enables to better reveal the differences between the theoretical and practical dimensions, between the collectiveness and the individual aspect of such a freedom of access and use of natural spaces. By allowing both one and all to invest in environmental values, the right of public access does not solve for all environmental injustice and conflict. Rather, frequent challenges, different interpretations of this right by the stakeholders and spatial cohabitation of many practices highlight the issue of the sharing of environmental capital. Hence, such sharing is expressed through spatial forms of contracts which often refer less to a segmentation of space than in forms of copresence. By allowing the public use of private lands (except for private spaces) and by promoting the non-rival valuation of natural spaces by different stakeholders, the right of public access enables to dissolve the distinction between public space and private space in favour of creating a contractual space.